Guiding waters reimagining barrier islands in an inland application for the flood resilience of the waterfront community of Tanay, Rizal - Jao, Katrina Bernice S.
Flood has, and will always be, a problem for archipelagic countries like ours. 36,000 kilometers of coastline remain vulnerable to flood events, and the consequential infrastructural and economic damage are more than what the Philippines can handle, considering the lack of flood resiliency methods. More than 60 percent of the country's inhabitants occupy water-land boundaries, with many communities further increasing susceptibility due to faulty drainage systems and trash buildup, not to mention rapid population growth and urbanization with no regards to sustainability and resiliency. More so, typhoons and storms, the main instigators of flood events, are foreseen to increase in frequency. With this in mind, the need for a development which aims to protect waterfront communities arises. The thesis will employ landscape interventions which, drawing from the functions of barrier islands, will introduce flood resistance and resilience to the waterfront community of Tanay, Rizal. The framework for this new approach to flood resilience will be derived from the mimicry of the different components and functions of barrier islands, except reversing its function as a whole: instead of keeping the water out, the waterfront development will be designed to redirect the water into the site, effectively delaying and storing the floodwaters. This thesis shall be achieved by considering the needs and wants of the concerned stakeholders, and what is most affected in the community during flood events: namely, their agricultural livelihood. Balancing those needs with the landscape architectural solutions will be the basis of this whole development. At its very core, it's an artificial reimagining of an existing natural system, one in which its very function is challenged and reinterpreted in order to provide effective flood resilience.